THE RELATIONSHIP OF SAFETY AND COMPONENTS OF TOLL ROADS SERVICE - Daniel Situmorang; Agus Taufik Mulyono; Imam Muthohar; Iljoon Chang (Himpunan Pengembangan Jalan Indonesia (HPJI), 2017)
Abstract Indonesia uses Minimum Service Standard to provide the good service on toll road while Korea uses Level of Service and Information Technology System to measure the service on toll road. With a different implementation of service on a toll road, there is a different result on safety. This study shows exactly which component has a big effect to influence the road safety based on Korean and Indonesian experts, and shows the weight of those components in affecting the road safety. This study uses descriptive-quantitative method with questionnaire data collection techniques. An analysis was performed using the Structural Equation Modeling method. The result shows that the contribution of toll road service based on Korean expert data (24.1%) is larger compared to that of Indonesian expert data (21.4%) in improving the road safety. The most important component of toll road service to improve the road safety based on Korean expert data is toll road condition (90.8%), and the second is safety tools (85.6%). On the other hand, the most important component of toll road service to improve the road safety based on Indonesian expert data is safety tools (74.2%), and the second is toll road condition (54%). Based on both results, the component which has the biggest effect on the road safety is human factor and the second is the road. Keywords: toll road service, road safety, Structural Equation Modeling, human factor Abstrak Indonesia menggunakan Standar Pelayanan Minimal untuk memberikan pelayanan yang baik di jalan tol sedangkan Korea menggunakan Tingkat Layanan dan Information Technology System untuk mengukur layanan di jalan tol. Dengan implementasi layanan yang berbeda, terdapat hasil yang berbeda pada keselamatan di jalan tol. Penelitian ini menunjukkan secara tepat komponen yang memiliki pengaruh besar untuk mempengaruhi keselamatan jalan berdasarkan tenaga ahli Korea dan tenaga ahli Indonesia, serta menunjukkan bobot komponen yang mempengaruhi keselamatan jalan. Penelitian ini menggunakan metode deskriptif- kuantitatif dengan teknik pengumpulan kuesioner data. Analisis dilakukan dengan menggunakan metode Structural Equation Modeling. Hasil analisis menunjukkan bahwa kontribusi layanan jalan tol berdasarkan data tenaga ahli Korea (24,1%) lebih besar dibandingkan dengan data tenaga ahli Indonesia (21,4%) dalam meningkatkan keselamatan di jalan. Komponen yang paling penting dari layanan jalan tol untuk meningkatkan keselamatan di jalan berdasarkan data tenaga ahli Korea kondisi jalan tol (90,8%), dan yang kedua adalah alat pengaman (85,6%). Di sisi lain, komponen yang paling penting dari layanan jalan tol untuk meningkatkan keselamatan di jalan berdasarkan data tenaga ahli Indonesia adalah alat pengaman (74,2%), dan yang kedua adalah kondisi jalan tol (54%). Berdasarkan kedua hasil tersebut, komponen terbesar yang memiliki pengaruh pada keselamatan jalan adalah faktor manusia dan yang kedua adalah jalan. Kata-kata kunci: pelayanan jalan tol, keselamatan jalan, Structural Equation Modeling, faktor manusia